Dilemmata der Nachhaltigkeit - Karafyllis, Nicole C.; Berg, Sophie; Bergmann, Matthias; Gruber, Holli; Henkel, Anna; Mader, Dimitri; Müller, Ann-Kristin; Siebenhüner, Bernd; Speck, Karsten; Zorn, Daniel-Pascal (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This volume contributes to a reflective perspective on dilemmas in research on and the implementation of sustainable development. Its contributions develop reflective perspectives on what can be considered dilemmas in relation to sustainability, what other forms of contradictions sustainability research encounters and how they can be dealt with. Empirical case studies cover subject areas such as urban planning, law, bioeconomy and medicine, investigating specific conflicts, contradictions and tensions that harbour the potential for dilemmas. Finally, the book discusses any challenges for academia and research in this field arising in theory, research practice and research funding. With contributions by Sophie Berg | Matthias Bergmann | Markus P. Beham | Claudia Bozzaro | Holli Gruber | Saskia Grüßel | Armin Grunwald | Gerhard de Haan | Anna Henkel | Jana Holz | Thomas Jahn | Nicole C. Karafyllis | Philip Koch | Sarah Kessler | Dominik Koesling | Henrike Rau | Dimitri Mader | Ann-Kristin Müller | Georg Müller-Christ | Stephan Lorenz | Laura Scheler | Bernd Siebenhüner | Mandy Singer-Brodowski | Karsten Speck | Stefan Staehle | Sebastian Suttner | Jörn Zitta | Daniel-Pascal Zorn.